2011
DOI: 10.1093/toxsci/kfr203
|View full text |Cite
|
Sign up to set email alerts
|

ERK Crosstalks with 4EBP1 to Activate Cyclin D1 Translation during Quinol-Thioether–Induced Tuberous Sclerosis Renal Cell Carcinoma

Abstract: The mammalian target of rapamycin (mTOR) and mitogen-activated protein kinase signaling cascades have been implicated in a number of human cancers. The tumor suppressor gene tuberous sclerosis-2 (Tsc-2) functions as a negative regulator of mTOR. Critical proteins in both pathways are activated following treatment of Eker rats (Tsc-2(EK/+)) with the nephrocarcinogen 2,3,5-tris-(glutathion-S-yl)hydroquinone (TGHQ), which also results in loss of the wild-type allele of Tsc-2 in renal preneoplastic lesions and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 59 publications
1
18
0
1
Order By: Relevance
“…MTORC1 can increase cyclin D1 expression via inactivation of eukaryotic initiation factor 4E-binding protein 1. 60,61,67,68 Previously, the MTOR was the only pathway known to be involved in acquiring classic markers of a senescent phenotype, including cyclin D1 accumulation. For the first time, we added an additional pathway, the MAPK pathway that is required, for the acquisition of at least one hallmark of senescence: hyperaccumulation of cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…MTORC1 can increase cyclin D1 expression via inactivation of eukaryotic initiation factor 4E-binding protein 1. 60,61,67,68 Previously, the MTOR was the only pathway known to be involved in acquiring classic markers of a senescent phenotype, including cyclin D1 accumulation. For the first time, we added an additional pathway, the MAPK pathway that is required, for the acquisition of at least one hallmark of senescence: hyperaccumulation of cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of 4E-BP leads to its dissociation from eIF4E, a key rate-limiting initiation factor for translation (18). Recently, the mTOR independent interaction of 4E-BP with the ERK/MAPK signaling pathway, which is differentially regulated in our mouse model, was discussed intensively (11,37). Several lines of evidence have suggested a role of oxidative stress in longevity.…”
Section: E500mentioning
confidence: 96%
“…Inhibitor of S6K (PF478671) only slightly decreased levels of cyclin D1, indicating that effects of rapamycin on cyclin D1 accumulation may involve different pathways. In fact, it was shown that MTOR increases cyclin D1 through inactivation of 4EBP1 55 , 56 . We also investigated 2 inhibitors of p90 RSK (SL 0101-1 and BRD7389).…”
mentioning
confidence: 99%